Design of Sterilizer Calibration With Esp8266 Based on Internet of Things - Anindyahadi, Fitri; Nugroho, Setyo Adi; Dewantara, Mahardira; Suyamto, Yuli (Journal of Energy and Electrical Engineering, 2025)
Advancing technology demands reliable monitoring of key indicators such as temperature, a fundamental measure of heat or cold and critical wherever stable setpoints are required. Guided by Industry 4.0 principles, this study develops an Internet-of-Things (IoT) sterilizer calibration tool using an ESP8266 controller for real-time access. The device was built as planned, from component selection and casing design to the accompanying application, and supports continuous temperature observation. The IoT layer simplifies data acquisition and provides reliable, real-time monitoring via the ESP8266. Experimental evaluation shows small deviations from setpoints: at 150 °C the mean error is 0.5 °C, and at 200 °C the mean error is 0.1 °C. Testing followed the Medical Device Calibration Work Method No. 044-18 (2020) for sterilizer performance. All results remain within the permitted tolerance of ±5 °C, indicating that the tool is suitable for use and can assist applications that require stable, precisely monitored temperature conditions.